2008
DOI: 10.1002/jnr.21976
|View full text |Cite
|
Sign up to set email alerts
|

MRG15, a component of HAT and HDAC complexes, is essential for proliferation and differentiation of neural precursor cells

Abstract: Neurogenesis during development depends on the coordinated regulation of self-renewal and differentiation of neural precursor cells. Chromatin regulation is a key step in self-renewal activity and fate decision of neural precursor cells. However, the molecular mechanism(s) of this regulation is not fully understood. Here, we demonstrate for the first time that MRG15, a chromatin regulator, is important for proliferation and neural fate decision of neural precursor cells. Neuroepithelia from Mrg15 deficient emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Here we describe the role of the proteasome in regulating the accumulation of MRG-1, a protein implicated in promoting the proliferative fate in various systems (Chen et al, 2009;Tominaga et al, 2005;Zhang et al, 2010). We found that reducing proteasome activity, or mutating the putative E3 ligase RFP-1, elevated the levels of MRG-1 and enhanced stem cell overproliferation.…”
Section: Role Of the Proteasome In Regulating Stem Cell Proliferationmentioning
confidence: 92%
See 4 more Smart Citations
“…Here we describe the role of the proteasome in regulating the accumulation of MRG-1, a protein implicated in promoting the proliferative fate in various systems (Chen et al, 2009;Tominaga et al, 2005;Zhang et al, 2010). We found that reducing proteasome activity, or mutating the putative E3 ligase RFP-1, elevated the levels of MRG-1 and enhanced stem cell overproliferation.…”
Section: Role Of the Proteasome In Regulating Stem Cell Proliferationmentioning
confidence: 92%
“…MRG-1 is necessary for proliferation of the primordial germ cells, with mutants lacking both maternal and zygotic activity completely lacking a germ line due to failure of the primordial germ cells to proliferate (Fujita et al, 2002). Additionally, the murine homologue of MRG-1, MRG15, promotes proliferation of neural precursor cells (Chen et al, 2009). Therefore, MRG-1 is a good candidate for a proliferative fate-promoting protein, the accumulation of which may be controlled through proteasomal degradation.…”
Section: Characterization Of Rfp-1 Involvement In the Proliferative Fmentioning
confidence: 99%
See 3 more Smart Citations